Effects of Regional Labour Markets on Migration Flows, by Education Level - Fredrik Carlsen; Kare Johansen; Lasse Sigbjorn Stambol (European Regional Science Association (ERSA), 2010)
European labour markets display large variations in unemployment rates across regions as well as between education groups. Insufficient labour force mobility is widely considered the main culprit behind regional unemployment disparities, but few studies have examined the link between interregional mobility and variation in unemployment rates across education groups. This paper employs administrative registers covering the entire Norwegian population to compute annual time series from 1994 to 2004 of migration flows and regional labour market conditions by educational level for 90 travel-to-work areas. We find that geographical disparities in unemployment rates are decreasing in education level, whereas the response of migration to fluctuations in regional unemployment rates is increasing in education level. Our results suggest that low regional mobility of low educated workers contributes to high unemployment disparities across regions and education groups as well as high overall unemployment.
Keywords: 330